Poisson generic sequences - Alvarez, Nicolás Alejandro (2022)
Years ago, Zeev Rudnick defined the Poisson generic real numbers by counting the number of occurrences of long blocks of digits in the initial segments of the expansions of the real numbers in a fixed integer base. Peres and Weiss proved that almost all real numbers, with respect to the Lebesgue measure, are Poisson generic, but they did not publish their proof. In this note, we first transcribe Peres and Weiss´ proof and then we show that there are computable Poisson generic instances and that all Martin-L"of random real numbers are Poisson generic.